(untitled) (Research, Society and Development, 2025)
Health Care plays a fundamental role in the care of patients with chronic diseases, being essential for health promotion, complication prevention, and continuity of treatment. In this context, health technologies have been increasingly used to optimize care management and strengthen patient autonomy. This study aimed to identify and analyze the technologies employed in Primary Health Care for managing these diseases in Brazil through a integrative literature review. The research was conducted in scientific databases (SciELO, LILACS, MEDLINE, and Web of Science), using descriptors in Portuguese, English, and Spanish. A total of 456 articles were identified, of which 15 met the inclusion criteria and formed the final sample. The results showed that the main technologies used include electronic medical records, telemedicine, mobile applications, wearable devices, and digital educational tools. Despite the benefits, challenges such as limited infrastructure, the need for professional training, and resistance to technology adoption were identified. It is concluded that the incorporation of technologies in Primary Health Care is essential for improving the management of chronic diseases but requires structural investments, continuous professional training, and monitoring the effectiveness of these innovations.